MUSEUM EXHIBITIONS AND THE DYNAMICS OF ARTISTS' DIALOGUE IN THE ERA OF SOCIAL CRISIS - Kertemelidou, Paraskevi (Design/Arts/Culture, 2024)
In April 2012, the Museum of Cycladic Art in Athens curated a solo exhibition featuring Jannis Kounellis, a radical artist associated with the Arte Povera movement. This exhibition served as a profound "response" to the economic and social crisis engulfing Greece during that period. Kounellis, renowned for his innovative approach, actively engaged with the museum's space by utilizing raw materials and commonplace objects. These objects, sourced from thrift stores in Athens, bore little resemblance to traditional works of art and were chosen deliberately to comment on the prevailing socio-economic conditions. Kounellis's exhibition revolved around the common person who had been profoundly affected by the social and economic turmoil, offering a poignant representation of his fears, losses, and aspirations.